The Influence of Servant Leadership on Job Performance through Employee Empowerment and the Dimensions of Organizational Commitment - Pulung Adi Nugroho; Unggul Kustiawan (Journal of General Education and Humanities, 2026)
Employee performance in educational institutions is frequently associated with leadership style, empowerment practices, and organizational commitment; however, comprehensive empirical models integrating these variables, particularly within private school contexts, remain underexplored. This study aims to analyze the influence of servant leadership on employee empowerment, examine the effect of empowerment on the three dimensions of organizational commitment (affective, normative, and continuance), assess their impact on job performance, and test the moderating role of perceived supervisor support. A quantitative research design was employed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). Data were collected from 161 private school teachers in Tangerang through purposive sampling and analyzed using SmartPLS 4. Measurement validity and reliability were confirmed prior to hypothesis testing, and structural relationships were evaluated through bootstrapping procedures. The findings indicate that servant leadership significantly enhances employee empowerment, and empowerment positively influences affective, normative, and continuance commitment. Among these dimensions, only affective commitment has a significant positive effect on job performance, whereas normative and continuance commitment do not. Furthermore, perceived supervisor support does not moderate the relationship between employee empowerment and the three commitment dimensions. The results highlight the pivotal role of empowerment and emotional attachment in driving teacher performance and underscore servant leadership as a strategic mechanism for strengthening empowerment in educational organizations.